Experimento em Túnel de Vento do Escoamento Atmosférico Dentro e acima de uma Floresta de Eucalipto - de Paula, Reginaldo R. C.; Meneguzzi, Cristiane C.; Máfia, Reginaldo G.; Faria, Juliana S.; Junior, Nelson W.; Faé, Jamily S. (Ciência e Natura, 2011)
.